Perubahan Kualitas Jalan Permukiman Kumuh Di Kelurahan Tegalsari Kota Tegal - Anggun Kumala Dewi; Sunarti Sunarti (Teknik PWK (Perencanaan Wilayah Kota), 2021)
The existence of slums in urban areas can hamper the growth of a city because it is considered to trigger a gap both social and economic, so the need for handling the slum conditions. Slum settlement handling activities are a concern of the central government at this time, one of which is in Tegalsari Urban Village, Tegal City. In 2014, Tegalsari Urban Village had a slum area of 31.43 hectares with slum points in 5 (five) RWs. The slum treatment activity in this kelurahan has been going on for 4 years which includes the improvement of environmental facilities and infrastructure. In 2019, the slum area in Tegalsari Urban Village will be reduced to 4.91 hectares. This indicates a change in the quality of the slums. Against this background, the purpose of this study is to analyze changes in the quality of slums in Tegalsari Urban Village, Tegal City, which are limited to aspects of the road environment. The method used in this study is a quantitative research method using a questionnaire with a sample of 92 households. The analysis used includes descriptive statistical analysis and scoring analysis. The results showed that there was an increase in the quality of road aspects in the Tegalsari slums which was proven by scoring. The quality of roads in this area was previously included in the medium category. The quality is improved after handling into a good category. The quality improvement has an impact on the mobility of the local community which makes the community more often use the neighborhood road in the slums of Tegalsari Urban Village.